Synthesis and Characterization of the Complexes of S3N3Cl3 with ThCl4 under Varying Conditions - Jadon, S.P.S. (Asian Journal of Chemistry, 2010)
The complexes of S3N3CI3 with ThCl4 were synthesised at normal and high temperature and pressure. Their chemical data have assigned these complexes C1 and C2 respectively as S3N3CI3·ThCI4, and trimer (S3N3CI3·ThCI4)3 out of which the former has hexadentated Th4+ while the latter complex has bidentated Th4+ bridging between S3N3CI3 units. This is supported by their electronic and EPR spectra which express that these complexes are of paramagnetic and good conductive nature subsequently with distorted hexagonal and triclinical geometrical array.